PENGARUH ORIENTASI KEWIRAUSAHAAN TERHADAP KEUNGGULAN KOMPETITIF PADA UKM INDUSTRI KREATIF DENGAN KAPASITAS INOVATIF SEBAGAI FAKTOR MEDIASI DALAM MASA PANDEMIK COVID-19 - Louis Utama; Oey Hannes Widjaja; Yenny Lego (STIE Wiyatamandala, 2020)
A dynamic business environment that includes entrepreneurs must adapt in order to gain competitive advantage. One thing that must be considered is the entrepreneurial orientation and innovative capacity to increase competitive advantage in companies engaged in the creative industry. The method used is by distributing questionnaires to 30 entrepreneurs who run creative industries in the fashion sector in Tanah Abang Market in order to be sampled. The results show that entrepreneurial orientation and innovative capacity directly and positive influence the company's competitive advantage.